Literasi keuangan, Pemanfaatan QRIS dan Kinerja Usaha Mikro dan Kecil (UMK) di Jakarta Selatan - Zulfa Devina Rahman; Savira Indriani (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This research aims to evaluate the potential impact of financial literacy and the adoption of QRIS (Quick Response Code Indonesian Standard) on the performance of Micro and Small Enterprises (MSEs) in Jakarta Selatan. Employing a quantitative methodology, the study encompassed a sample of 30 MSEs selected through convenience sampling. Data collection was conducted via the dissemination of questionnaires, and the data was subsequently analyzed using multiple linear regression analysis with SPSS version 27. The findings of the study reveal a positive and statistically significant relationship between financial literacy, the utilization of QRIS, and the performance of MSEs in Jakarta Selatan. These results underscore the importance of enhancing financial literacy and promoting QRIS adoption to improve the performance of micro and small businesses in the region.